Trends in Ischemic Mitral Regurgitation Following ST-Elevation Myocardial Infarction Over a 20-Year Period - Perl, Leor; Bental, Tamir; Orvin, Katia; Vaknin-Assa, Hana; Greenberg, Gabriel; Codner, Pablo; Shapira, Yaron; Vaturi, Mordehay; Sagie, Alexander; Kornowski, Ran (Frontiers in Cardiovascular Medicine, 2022)
Background: Ischemic mitral regurgitation (IMR) is a common complication of acute ST-elevation myocardial infarction (STEMI). Little is known regarding the impact of IMR over a long period of follow up. Methods: Of 3,208 consecutive STEMI patients from a prospective registry, full echocardiographic information was available for 2,985 patients between the years 2000 and 2020. We compared the two decades- 2001 to 2010 and 2011 to 2020, and assessed for the presence of IMR at baseline, 3 (range 2–6) months and 12 (range 10–14) months after the index event. Results: One thousand six hundred and sixty six patients were included in the first decade, 1,319 in the second. Mean patient age was 61.3 ± 12.3 years, 21.1% female patients in the first decade vs. 60.9 ± 12.0 years and 22.2% female in the second (p = 0.40 and p = 0.212, respectively). Rates of moderate IMR or above during the index admission were 17.2% in the first period and 9.3% in the second one (p < 0.001). After 3 months, the rate of IMR was 48.5% for those who suffered from IMR at baseline, vs. 9.5% for those without IMR at baseline (HR- 4.2, p < 0.001). Death rates for those with moderate IMR or above were 14.7% and 17.8% after 1 and 2 years, respectively, vs. 7.3 and 9.6% for those without (p < 0.001 for both). IMR was associated with 1 year mortality in multivariate analysis (HR-1.37; 1.09–2.20, p = 0.009), as well as in propensity score matched analysis (HR 1.29; CI: 1.07–1.91; p < 0.001). Conclusions: IMR is a common complication following acute STEMI, impacting prognosis. Rates of IMR have declined significantly over the years.